2009
DOI: 10.4067/s0717-97072009000400032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Determination of a New Chalcone 1,5-Bis(3-Methyl-2-Thienyl)penta-1,4-Dien-3-One, C15h14os2

Abstract: This is a structure in a family concerning new polythiophene derivatives. This kind of compounds, a chalcones, has interesting aspects about its intermolecular interactions, of varied type (C-H···O, C-H···π, π···π) and strength. In the case of the title compound, C 15 H 14 OS 2 , interactions of all three types generate a rather compact, evenly connected 3D structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Frontier Molecular Orbitals (FMOs) were used to estimate the most reactive position in the πconjugated system and to describe many forms of reactions [26]. The energy values of the lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO) and their energy difference (ΔE) represent the molecule's reactivity.…”
Section: Frontier Molecular Orbitalsmentioning
confidence: 99%
“…Frontier Molecular Orbitals (FMOs) were used to estimate the most reactive position in the πconjugated system and to describe many forms of reactions [26]. The energy values of the lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO) and their energy difference (ΔE) represent the molecule's reactivity.…”
Section: Frontier Molecular Orbitalsmentioning
confidence: 99%
“…The C-C bond length of the cyclohexanone moiety (1.499(5)Å to 1.533(5)Å) are normal single bonds. Similarly, the bond lengths within thiophene rings which include S1 atom are between 1.341 (8)Å and 1.726 (4)Å, which include S2 atom are between 1.378 (6)Å and 1.733(4)Å which exhibit that the rings have the aromatic character [30].…”
Section: X-ray Structure Analysis and Computational Studiesmentioning
confidence: 94%
“…In Table 2, theoretical studies indicated that the shorting of the C=C double bonds (C5=C6, C10=C12) showing the partial double bond character of the C=C bands which are influenced by adjacent conjugated double bonds. Also, the conformation of these molecules is the result of the interaction between the electronic pair of oxygen in the carbonyl group [30].…”
Section: X-ray Structure Analysis and Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,9 In general there is not much structural information about this class the compounds. The structural information available is related to conformational studies and crystal structure as electronic interactions between oxygen of carbonyl group and the heteroatom 5,7,9 and interatomic interactions of type C-H…O, C-H…p, p…p 10,11 Following our interest in this kind of compounds, mainly directed to their use as potential ligands in further complex development we have synthesized and characterized a new compound in this populous family, viz: ir Spectrum Spectra of 1-(2-thienyl)-3-(3-methyl-2-thienyl)-propenone in KBr pellets were recorded on a FTIR-NICOLET MAGNA 550 spectrometer.…”
Section: 5mentioning
confidence: 99%